Stella M. Kirkendall letter to Nicholas S. Halmi regarding fall migration, 1976 - Kirkendall, Stella M.et al (1976)
Fall migration report contributed by Stella M. Kirkendall in a letter to Nicholas S. Halmi, December 16, 1976. This item was used as supporting documentation for the Iowa Ornithologists' Union Quarterly field report of fall 1976. Epson - sheet feed/flatbed